Expanding Opportunities for the Next Generation : Early Childhood Development in the Middle East and North Africa - El-Kogali, Safaa (Washington, DC: World Bank, 2015)
Early childhood is the most important stage of human development. In the Middle East and North Africa (MENA), there is little research and inadequate investment in this crucial stage of life. This book assesses the state of early childhood development (ECD) in MENA from before birth through age five, examining multiple dimensions of early development including health, nutrition, socio-emotional development, early learning, and early work. The book begins with a discussion of the importance of ECD as a critical foundation for later development, and also as a stage of life when inequality and social exclusion begin. ECD in MENA is set in a global context, and then countries within MENA are compared, with chapters on ECD in Algeria, Djibouti, Egypt, Iraq, Jordan, Lebanon, Libya, Morocco, Syria, Tunisia, West Bank and Gaza, and Yemen. As well as illustrating the state of ECD, the chapters assess risk and protective factors for early development and the extent of inequality in early childhood. A discussion of policies and programs that can enhance ECD illustrates how inequality and shortfalls in early development can be effectively addressed. This book will be of interest to anyone interested in the state of human development and inequality in MENA.